2018
DOI: 10.1016/j.fcr.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen supply and sink demand modulate the patterns of leaf senescence in maize

Abstract:  Authors can share their preprint anywhere at any time.  If accepted for publication, we encourage authors to link from the preprint to their formal publication via its Digital Object Identifier (DOI). Millions of researchers have access to the formal publications on ScienceDirect, and so links will help your users to find, access, cite, and use the best available version.  Authors can update their preprints on arXiv or RePEc with their accepted manuscript .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 52 publications
2
47
0
Order By: Relevance
“…with the sole proso millet treatment at maturity (Table 3). These results are in good agreement with a previous work on maize plants where nitrogen supply increased photosynthetic activity and delayed the leaf senescence (Lima et al 1999, Kitonyo et al 2018. These findings suggested that intercropping treatment is important in delaying the progress of proso millet leaf senescence, and increases the activities of photosynthetic reaction centers and improves electron transfer quantum efficiency of PSII and excess light energy utilization, which might decrease excess energy dissipation as heat.…”
Section: Yearsupporting
confidence: 92%
“…with the sole proso millet treatment at maturity (Table 3). These results are in good agreement with a previous work on maize plants where nitrogen supply increased photosynthetic activity and delayed the leaf senescence (Lima et al 1999, Kitonyo et al 2018. These findings suggested that intercropping treatment is important in delaying the progress of proso millet leaf senescence, and increases the activities of photosynthetic reaction centers and improves electron transfer quantum efficiency of PSII and excess light energy utilization, which might decrease excess energy dissipation as heat.…”
Section: Yearsupporting
confidence: 92%
“…Third, because the senescence process is also influenced by a range of environmental factors, such as low nutrient supply, photoperiod, temperature, and drought ( Lim et al, 2007 ; Schippers et al, 2015 ; Santos Matos, 2020 ), small variations in the environment may affect the leaf senescence intensity promoted by the hyperactive ACD6 allele. Several genetic analyses pointed out that both the onset and the duration of leaf senescence act on the grain filling in crop plants ( Hafsi et al, 2000 ; Gregersen et al, 2013 ; Xie et al, 2016 ; Kitonyo et al, 2018 ). For instance, Xie et al (2016) showed that a delayed but fast leaf senescence promoted grain-filling rates in bread wheat.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of increased chlorophyll meter measurements with an increase of PGR rate for Expt. 2 could have been due to the use of foliar resources for inflorescence development (Kitonyo et al, 2018;Leopold, 1961). Interestingly, chlorophyll meter measurements for Expt.…”
Section: Discussionmentioning
confidence: 99%